Experimental Study on Creep Behavior and Crack Evolution of Stratified Structural Sandstone under Segmental Constant Load - Yiran Yang; Yanzhong Li; Jiaojiao Pan; Tao Luo; Zidong Lu (Geofluids)
The hazards induced by stratified rock mass creep are still one of the major problems that threaten the safety of underground engineering. This paper takes safe construction of underground roadway in Urumqi mining area as the research background. In this study, we mainly adopted rock mechanics experiments to accomplish the research on creep behavior and crack evolution of stratified structural sandstone. Creep deformation characteristics of stratified structural sandstone under different load were revealed; also, we analyzed the reason why a part of rock samples failed but others were not under the same load. Creep behavior and crack evolution of rock samples without stratified structure have significant randomness. The crack evolution and failure characteristics of stratified structural rock samples were mainly manifested as failure along and cutting through structural plane and their combined forms. Creep strain, creep duration, and creep rate of rock samples with stratified structure had a nonlinear relationship with applied load, such as exponential function or logarithmic function. Understanding the evolutionary relationship between the above parameters and load provides a basis for obtaining the creep behavior of stratified rock mass under different load conditions.